2019
DOI: 10.3389/fphar.2019.00026
|View full text |Cite
|
Sign up to set email alerts
|

Hsp60 as a Novel Target in IBD Management: A Prospect

Abstract: Inflammatory bowel disease (IBD) encompasses various pathological conditions similar but distinct that share a multifactorial etiology, including involvement of the intestinal barrier function, the immune system, and intestinal microorganisms. Hsp60 is a chaperonin component of the chaperoning system, present in all cells and tissues, including the intestine. It plays important roles in cell physiology outside and inside mitochondria, its canonical place of residence. However, Hsp60 can also be pathogenic in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…It is thought that they may be related to: Alteration of Treg/Th17 due to dysregulated TLRs on antigen-presenting cells [27];Resistance to colonization, i.e., ability of the gut microbiota to limit the proliferation of external pathogens. It has been observed that in patients with autoimmune disorders (e.g., systemic lupus erythematosus), resistance to colonization was lower than in healthy controls;Superantigens, derived from bacteria and viruses that have the ability to activate immune cells by simultaneously binding to the major proteins of the class II histocompatibility complex (MHC II) present in the antigen-presenting cells and to specific receptors present in activated T cells [32];Alteration of host antigens and overproduction of autoantigens; in particular, microbiota induces modification of host proteins and creation of neoantigens [27,33];Mucosal responses to microbiota, i.e., inflammatory cytokines that activate nearby autoreactive cells [30];Molecular mimicry, i.e., cross-reactive antibody that recognizes shared epitopes of microbial and host tissue proteins, and activation of autoreactive T and B cells [29,34,35]. …”
Section: Pathobiology Of Alu In Ibd and Therapeutic Proposalmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that they may be related to: Alteration of Treg/Th17 due to dysregulated TLRs on antigen-presenting cells [27];Resistance to colonization, i.e., ability of the gut microbiota to limit the proliferation of external pathogens. It has been observed that in patients with autoimmune disorders (e.g., systemic lupus erythematosus), resistance to colonization was lower than in healthy controls;Superantigens, derived from bacteria and viruses that have the ability to activate immune cells by simultaneously binding to the major proteins of the class II histocompatibility complex (MHC II) present in the antigen-presenting cells and to specific receptors present in activated T cells [32];Alteration of host antigens and overproduction of autoantigens; in particular, microbiota induces modification of host proteins and creation of neoantigens [27,33];Mucosal responses to microbiota, i.e., inflammatory cytokines that activate nearby autoreactive cells [30];Molecular mimicry, i.e., cross-reactive antibody that recognizes shared epitopes of microbial and host tissue proteins, and activation of autoreactive T and B cells [29,34,35]. …”
Section: Pathobiology Of Alu In Ibd and Therapeutic Proposalmentioning
confidence: 99%
“…Mucosal responses to microbiota, i.e., inflammatory cytokines that activate nearby autoreactive cells [30];…”
Section: Pathobiology Of Alu In Ibd and Therapeutic Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…We have explored the deployment of Heat Shock Protein 60 (Hsp60) as a possible autoantigen in IBD, due to the implication of Hsp60 in inflammatory processes [22,23,24,25,26,27,28,29,30,31], including IBD [32,33,34,35]. Heat shock proteins are a broad family of molecular chaperons capable of reacting to cellular stress, especially in thermal changes.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp60, despite being a protein whose main function occurs in the mitochondria, is able to act in the cytoplasm modulating the immune response associated with inflammation. Both the complete protein and the peptides derived therefrom can act as natural regulators of the inflammatory reaction together with other cytokines, chemokines, and autoantibodies, regulating the immune system [30,32,36,37,38,39]. The activity of Hsp60 has been associated with various autoimmune and inflammatory pathologies, such as atherosclerosis, diabetes, rheumatoid arthritis, or multiple sclerosis [23,25,29,40,41,42].…”
Section: Introductionmentioning
confidence: 99%